ACETONE-BUTANOL-ETHANOL FERMENTATION FOR BIOENERGY USING VARIOUS SUBSTRATES IN DEFINED TYA MEDIA - Hanies Ambarsari; Kenji Sonomoto (Badan Pengkajian dan Penerapan Teknologi, 2015)
A series of experiments had been conducted to investigate the performance of Clostridiumsaccharoperbutylacetonicum strain N1-4 (ATCC 13564) in direct fermentation of acetone, butanol, andethanol (ABE) using several substrates that have not been investigated previously using this strain,such as cellobiose, dextrin, starches of corn, potato, tapioca, wheat, and sago, as well as morecomplex carbohydrates such as xylans, cellulose, and carboxyl methyl cellulose (CMC), particularly tostudy the effect of such various substrate types and concentrations, as well as the substrates mixtureson the ABE ratio and productivity. The results showed that strain N1-4 could directly produce ABE fromvarious substrates, from monosaccharide to polysaccharides of hexose or pentose sugars, exceptCMC and cellulose. The experiments also suggested that cellobiose (a hexose disaccharide) could bethe more efficient substrate for strain N1-4 than glucose (a monosaccharide) to produce ABE in the TYA(Tryptone Yeast Agar) medium. It was proven also that the ABE ratio was very dependent on the typeand concentration of substrates being used by strain N1-4.Keywords: acetone, butanol, ethanol, clostridium saccharoperbutylacetonicum N1-4, fermentation